A New Approach to High Value Conversion of Phosphogypsum from Phosphate Rock to Catalyst for Glycerol Carbonate Synthesis. Issue 1 (March 2021) - Wang, Y S; Wang, Y X; Tang, M Z; Yang, G; Sun, Y
Abstract: This paper reports a new process of using phosphate rock as the precursor to prepare a high performance catalyst for glycerol carbonate synthesis. The reported technical route will create a new opportunity to synthesis the active chemical intermediate that can be used for energy generation. Three important preparation parameters were investigated to find out both singular and binary effects upon the statistical significances of prepared glycerol carbonate conversion using response surface methodology (RSM) approach. The optimal condition with the goal of maximizing the glycerol carbonate was set and achieved. The obtained catalyst prepared at the optimal condition was characterized. The proposed process offers a rosy prospect for high value conversion of colossal by-product phosphogypsum generated from phosphorous acid manufacturing industry.